Acoustic and articulatory analysis and synthesis of shouted vowels. (March 2021) - Xue, Yawen; Marxen, Michael; Akagi, Masato; Birkholz, Peter
Highlights: Acoustic and articulatory differences between spoken and shouted vowels were analyzed for two male and two female subjects by means of acoustic recordings and midsagittal magnetic resonance images of the vocal tract. Fundamental frequencies, intensities, and formant frequencies were all generally higher for shouted than for spoken vowels. The harmonics-to-noise ratios and H1-H2 measures were generally lower for shouted vowels than for spoken vowels. All subjects used an increased lip opening, an increased jaw opening, and a lower tongue position for shouted vowels. However, the changes of vertical larynx position, uvula elevation, and jaw protrusion between spoken and shouted vowels were inconsistent among subjects. Perception experiments were conducted to examine how changes of fundamental frequency, subglottal pressure, vocal tract shape, and phonation type contribute to the perception of stimuli created by articulatory synthesis as being shouted. Here, fundamental frequency had the greatest effect, followed by vocal tract shape and lung pressure, with no measurable effect of phonation type. Abstract: Acoustic and articulatory differences between spoken and shouted vowels were analyzed for two male and two female subjects by means of acoustic recordings and midsagittal magnetic resonance images of the vocal tract. In accordance with previous acoustic findings, the fundamental frequencies, intensities, and formant frequencies were all generally higher for shouted than for spoken vowels. The harmonics-to-noise ratios and H1-H2 measures were generally lower for shouted vowels than for spoken vowels. With regard to articulation, all subjects used an increased lip opening, an increased jaw opening, and a lower tongue position for shouted vowels. However, the changes of vertical larynx position, uvula elevation, and jaw protrusion between spoken and shouted vowels were inconsistent among subjects. Based on the analysis results, a perception experiment was conducted to examine how changes of fundamental frequency, subglottal pressure, vocal tract shape, and phonation type contribute to the perception of stimuli created by articulatory synthesis as being shouted. Here, fundamental frequency had the greatest effect, followed by vocal tract shape and lung pressure, with no measurable effect of phonation type.